The fusion product losses due to resonant magnetic perturbations in toroidal plasmas - Moskvitina, Yu.K.; Moskvitin, A.O.; Shyshkin, O.A. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
The suppression of edge-localized modes (ELMs) by means of the externally applied resonant magnetic field perturbations (RMPs) and its effect on plasma transport is investigated actively on modern tokamaks. In present paper the modification of loss rates of fusion born alpha particles caused by application of RMPs in tokamak plasma is examined. This study has been performed by means of test-particle simulations. To simplify calculations we use magnetic field model with circular magnetic surfaces. The transport properties of alpha particles are investigated during 3 seconds time interval by tracing the test-particle ensemble. Each particle trajectory is calculated by means of integration of full orbit equations. Three regimes of particle losses are identified during the evolution of the particle ensemble. The formation of magnetic islands together with the stochastic magnetic layers at the plasma edge is the natural consequence of RMPs excitation. It is demonstrated that due to the formation of these resonant magnetic field structures the irregularities of energetic alpha particle orbits occur, and hence the substantial increasing of the losses from the plasma periphery is observed. RMPs slightly affect the first orbit losses of fusion alphas. Подавление гранично-локализованных мод (ELMs) внешними резонансными магнитными возмущениями (RMPs) и их влияние на перенос плазмы активно изучается на современных токамаках. В работе рассматривается изменение скорости потерь термоядерных альфа частиц при наличии RMPs в токамаках. Данное исследование проведено в одночастичном приближении. Для упрощения вычислений в работе используется модель магнитного поля с круглыми магнитными поверхностями. Свойства переноса альфа частиц изучаются путем моделирования движения ансамбля пробных частиц в течение 3 секунд. Траектория каждой частицы рассчитывалась на основании уравнения полной орбиты. При исследовании эволюции ансамбля частиц были выделены 3 режима потерь. Образование магнитных островов со стохастическими слоями на периферии плазмы является естественным следствием использование RMPs. Показано, что образование этих резонансных структур в топологии магнитного поля приводит к нерегулярному поведению орбит энергичных альфа частиц, и, следовательно, наблюдается существенное увеличение потерь этих частиц. RMPs слабо влияют на потери альфа частиц на первой орбите. Послаблення гранично-локалізованих мод (ELMs) зовнішніми резонансними магнітними збуреннями (RMPs) та їх вплив на транспорт плазми активно вивчається на сучасних токамаках. В роботі розглядається зміна швидкості втрат термоядерних альфа частинок за наявності RMPs у токамаках. Дане дослідження проведено в одночастинковому наближенні. Для спрощення розрахунків у роботі використовується модель магнітного поля з круглими магнітними поверхнями. Властивості транспорту альфа частинок вивчаються шляхом моделювання руху ансамблю пробних частинок протягом 3 секунд. Траєкторія кожної частинки розраховувалася на основі рівняння повної орбіти. При дослідженні еволюції ансамблю частинок були виділені 3 режими втрат. Утворення магнітних островів зі стохастичними шарами на периферії плазми є природнім наслідком використання RMPs. Показано, що утворення цих резонансних структур у топології магнітного поля призводить до нерегулярної поведінки орбіт енергійних альфа частинок, і, як наслідок, спостерігається значне підвищення втрат цих частинок. RMPs слабо впливають на втрати альфа частинок на першій орбіті.
Keywords: RMPs; потери продуктов синтеза; уравнение полной орбиты; альфа-частица; fusion product losses; full orbit; alpha particle